GRAIN YIELD, WATER USE EFFICIENCY, ECONOMICS AND SOIL MOISTURE EXTRACTION PATTERN OF SUMMER GREENGRAM (VIGNA RADIATA VAR. RADIATA) AS INFLUENCED BY PLANTING AND IRRIGATION METHODS; IRRIGATION SCHEDULES AND VAM INOCULATION - Singh, RAMAN JEET; IDNANI, L.K.; RAI, R.K (Annals of Agricultural Research, 2014)
A field experiment was conducted to study the response of summer greengram to the irrigation regimes (two irrigations at pre-flowering and pod filling stages and three irrigations at branching, pre-flowering and pod filling stages), four planting and irrigation methods (flat bed planting and irrigation ridge planting and furrow irrigation, ridge planting and alternate furrow irrigation, furrow planting and irrigation method) and two levels of VAM (control and inoculation). The experiment was laid out in a split plot design with three replications. Greengram cultivar 'Pusa Vishal' produced significantly higher grain yield and had markedly higher net return and benefit: cost ratio under three irrigations, one each at branching, pre-flowering and pod filling stages by furrow planting and irrigation method with VAM inoculation. However, the water use efficiency was higher with two irrigations one each at pre-flowering and pod filling stages. So, an increase in irrigation frequency increased the seasonal water use but decreased the water use efficiency. The higher soil moisture was extracted under two irrigations at pre-flowering and pod filling stages applied by ridge planting and alternate furrow irrigation method without VAM (0-15 cm soil depth).